SYLLABLE IS THE BASIC SUPRASEGMENTAL UNIT IN PHONETICS IN ENGLISH. (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the role of the syllable as a fundamental suprasegmental unit in English phonetics and phonology. It examines the internal structure of syllables, including onsets, nuclei, and codas, and discusses their phonetic composition and variations. The study highlights the importance of syllables in stress placement, vowel reduction, and rhythm, which collectively shape the characteristic prosody of English as a stress-timed language. Additionally, it analyzes how syllables influence phonological processes such as assimilation, elision, and liaison in connected speech. The interaction between syllables and intonation patterns is also considered, emphasizing their contribution to speech melody and communicative meaning. Finally, the article addresses dialectal differences in syllable realization, illustrating the adaptability and variability of syllabic structures across English varieties. Understanding the syllable’s multifaceted role provides essential insights into the dynamics of English speech production and perception.